2011
DOI: 10.1007/s10832-011-9649-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of lanthanum doping on magnetic properties of nano cobalt ferrites

Abstract: The magnetic properties of nano-crystallite cobalt lanthanum ferrite (CoLa x Fe 2-x O 4 ) with varied quantities of lanthanum (x=0, 0.1, 0.15, 0.2, 0.25, 0.3) prepared by coprecipitation method have been studied by vibrating sample magnetometer (VSM) and LCR meter. X-ray diffraction (XRD) and transmission electron microscopy (TEM) confirmed the size, structure, and morphology of the ferrite samples. The average crystallite size varied from 17.83 nm to 49.99 nm. All the samples, although, in nano range, show si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The total magnetization of cobalt ferrite is the difference between the magnetization of B and A sites, and consequently the magnetization is reduced at room temperature. 53 It is observed that for pure cobalt ferrite with a crystallite size of 46 nm, a M s value of 80 emu g À1 is found at 300 K, which is in good agreement with the reported value (76 emu g À1 ). 54 Moreover, the doping of Gd 3+ ions in cobalt ferrite monotonically decreases the value of the saturation magnetization from 80 to 53.8 emu g À1 when the crystallite size of the Gd 3+ doped cobalt ferrite decreases from 40 to 23 nm.…”
Section: Magnetic Studysupporting
confidence: 89%
See 1 more Smart Citation
“…The total magnetization of cobalt ferrite is the difference between the magnetization of B and A sites, and consequently the magnetization is reduced at room temperature. 53 It is observed that for pure cobalt ferrite with a crystallite size of 46 nm, a M s value of 80 emu g À1 is found at 300 K, which is in good agreement with the reported value (76 emu g À1 ). 54 Moreover, the doping of Gd 3+ ions in cobalt ferrite monotonically decreases the value of the saturation magnetization from 80 to 53.8 emu g À1 when the crystallite size of the Gd 3+ doped cobalt ferrite decreases from 40 to 23 nm.…”
Section: Magnetic Studysupporting
confidence: 89%
“…10 (a, b). The total magnetization of cobalt ferrite is the difference between the magnetization of B and A sites, and subsequently reduces the magnetization at room temperature 53 . The saturation magnetization (M s ), the coercivity (H c ) and the remanance magnetization (M r ) at 300 K and 10 K are given in Table 3.…”
Section: Fe-sem and Eds Analysismentioning
confidence: 99%
“…At first sight, the Raman spectra of our particles exhibit clearly broadened bands compared with bulk CoFe 2 O 4 . This feature is quite common in nanostructures (Yu et al, ; Tahar et al, ; Kumar et al, ). Moreover, the bands above 600 cm −1 , related to the two A 1g modes, are found to overlap, in accordance with previous works on nanocrystalline spinel ferrites (da Silva et al, ; Kumar et al, ).…”
Section: Resultsmentioning
confidence: 94%
“…A rapid overview of the relevant literature shows that chemically made (Co 1 − x Zn x )Fe 2 O 4 nanocrystalline solid solutions exhibit a maximal magnetization at x ranging between 0.4 and 0.5 (Sharifi and Shokrollahi, ; Tahar et al, ; Ghasemian et al, ; Tatarchuk et al, ). In the case of Co(Fe 1 − x Ln x )O 4 nanocrystalline solid solutions, the highest magnetization was obtained for Ln = Gd and x ~ 0.1, the solubility limit of Ln cations being of the same order (Tahar et al, ; Kumar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the spinel ferrites have the resourceful magnetic and electrical properties among other ferrites. In particular, CoFe 2 O 4 has attracted considerable attention because of its structural, magnetic and electrical conductivity under a range of conditions [16][17][18][19] Furthermore, CoFe 2 O 4 possesses a partially inverse structure with a degree of inversion that depends on the method of preparation and heat treatment 20 21 CoFe 2 O 4 has a spinel crystal structure and crystallizes in a cubic close packed structure of oxygen ions, in which tetrahedral [A] and octahedral [B] sites are occupied by cations. At the same time, the magnetization, coercivity, permittivity and conductivity are greatly affected by the porosity, grain size and microstructure of the sample.…”
Section: Introductionmentioning
confidence: 99%